Identification of salt-tolerant cultivars and plant traits in wheat during germination and seedling emergence stages - Lin Zhao; Simeng Li; Xuemei He; Hanyu Liu; Yiran Cheng; Yi Wang; Houyang Kang; Jian Zeng (Plant, Soil and Environment)
In this study, we assessed the salt tolerance of 38 wheat cultivars from primary wheat cultivation regions in China using a membership function value (MFV) during the germination and seedling emergence stages. Based on salt tolerance assessment, three contrasting groups were classified, with 10 tolerant, 23 moderately tolerant and 5 sensitive cultivars under low salt stress, and 4 tolerant, 25 moderately tolerant and 9 sensitive cultivars under high salt stress and in addition to Na+ and K+ homeostasis regulation, nitrogen efficient transfer from seed to plant tissues denoted the significant positive correlation with salt tolerance, confirming the importance of nutrient spectra organisation. Salt-tolerant and moderately tolerant cultivars had lower trait network modularity than salt-sensitive cultivars, demonstrating that wheat with different salt tolerance uses alternative strategies to cope with salt stress. These results were important for germplasm evaluation and variety breeding of salt tolerance in wheat.